Ethanol production in a simultaneous saccharification and fermentation process with interconnected reactors employing hydrodynamic cavitation-pretreated sugarcane bagasse as raw material - Hilares, RT (2017)
The authors gratefully acknowledge the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCyTEC-Perú, process number 219-2014) and Conselho Nacional de Desenvolvimento Científico e Tecnológico (CNPq-Brazil, process number 449609/2014-6) for financial support.